Pengaruh Institutional Ownership, Profitability dan Leverage Terhadap Kondisi Financial Distress pada Perusahaan Manufaktur yang Listed Di BEI - Ferdian Ferdian (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2019)
This research was conducted to examine the effect of the variable (X_1) Institutional Ownership with measuring instruments using the KINS dimension, (X_2) Profitability with measuring instruments using the dimensions of return on assets and (X_3) Leverage with measuring instruments using the dimensions of debt to total assets, against (Y) financial distress with measuring instruments using the dimension of earnings per share in manufacturing sector companies listed on the IDX for the 2011-2015 period. The sampling technique used stratified random sampling, a sample of 30 companies from 151 companies that have complete criteria. The analysis technique used is multiple regression random effect method and hypothesis testing, the analysis shows that the Institutional Ownership variable partially has a significant and positive effect.at the level of significance of 5%, but partially there is no significant and positive effect on Profitability, while on the Leverage variable partially there is a significant and negative effect on Financial Distress. Simultaneously, Institutional Ownership, Profitability and Leverage are not proven to have a significant effect on financial distress in manufacturing sector companies listed on the IDX at a level of significance greater than 5%. The predictive ability of the three variables on Financial Distress is 3.37%, while the remaining 96.3% (100% - 3.37%) is explained by other variables that are not researched or not included in this research model.